Sears list of subject headings - Miller, Joseph, 1946-; McCarthy, Susan, 1958-; Sears, Minnie Earl, 1873-1933. (New York : H.W. Wilson Co., 2010)
The book is a list of subject headings used in information retrieval and organisation
Includes bibliographical references (p. xl-xli).
uaj 23/04/2013
Ref.
Keywords: Subject headings: List of subject headings